Childfree from the Perspective of Islamic Feminism: An Analysis of the Thoughts of Amina Wadud and Asma Barlas - Afidatul Khasanah; Rajabbul Amin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The phenomenon of childfree, the decision not to have children, is increasingly becoming a concern in social discourse, especially in the context of modern society which is dominated by the concepts of gender justice and bodily rights. This article analyzes the issue of childfree from the perspective of Islamic feminism through the thoughts of Amina Wadud and Asma Barlas. The main focus of this article is to understand how these two thinkers interpret women's rights, especially regarding the freedom to choose their reproductive roles. Using a qualitative method based on literature study, this research asserts that Islamic feminism, as initiated by Wadud and Barlas, supports women's right to choose childfree as a form of bodily autonomy and moral freedom guaranteed in Islamic teachings. This article also seeks to criticize patriarchal interpretations that limit women to domestic roles. The results show that the childfree decision can be categorized as a form of women's liberation from social pressure that is not in accordance with the principles of justice and equality in Islam.